Variation in level of entry of the vertebral artery into the transverse foramen - Dodevski, Ace; Lazareska, Menka; Chadikovska, Elizabeta; Aliji, Vjolca; Janevski, Petar (Macedonian Association of Anatomists and Morphologists, 2011)
The aim of this study was to analyze the variable level of entrance into the transverse foramen and to point the risks of injury of the vertebral artery during accomplishing surgical procedures. For that purpose we examined 40 patients with CT angiography and analyzed the level of entrance into the transverse foramen. The vertebral artery entered the C6 transverse foramen in 38 (95%) patients. Abnormal level of vertebral artery entrance was observed in two (5%) patients, with entrance into the C4 and C5 transverse foramen. The incidence of abnormal level of entrance into the transverse foramen is relatively high, and this potentially dangerous condition should be detected on preoperative imaging in order to avoid vertebral artery injury.
Варијации во нивото на влез на 'рбетната артерија во напречниот отвор
Keywords: anatomy; vertebral artery; transverse foramen; cervical spine; surgery